2015
DOI: 10.1002/cb.1566
|View full text |Cite
|
Sign up to set email alerts
|

How do shoppers behave online? An observational study of online grocery shopping

Abstract: The pace of online shopping revenue growth means it is important for retailers and manufacturers to understand how consumers behave online compared with their behaviour in brick and mortar stores. We conducted a study in which the detailed behaviour of 40 shoppers was screen recorded while they each undertook an online shopping 'trip'. The shopping trip comprised purchasing a basket of 12 commonly bought grocery categories at one of two major retailers. The shoppers were all inexperienced in online grocery sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 49 publications
5
92
0
Order By: Relevance
“…As similarities and differences between VSS and actual shopper behaviour have been quite well established for single category testing in desktop VSS shopping, we report a differentiated replication that checks some key results from the VSS literature, but also examines a broader set of in‐store behaviours within an immersive VSS environment. This approach is similar to that of Anesbury, Nenycz‐Thiel, Dawes, and Kennedy (), who documented online shopper behaviour in an exploratory manner, with benchmarks for validation drawn from prior work in the physical retailing literature. The results of the present study will indicate whether immersive VSS experiments lead to authentic shopper behaviour usable by market researchers and in consumer behaviour experiments.…”
Section: Introductionmentioning
confidence: 99%
“…As similarities and differences between VSS and actual shopper behaviour have been quite well established for single category testing in desktop VSS shopping, we report a differentiated replication that checks some key results from the VSS literature, but also examines a broader set of in‐store behaviours within an immersive VSS environment. This approach is similar to that of Anesbury, Nenycz‐Thiel, Dawes, and Kennedy (), who documented online shopper behaviour in an exploratory manner, with benchmarks for validation drawn from prior work in the physical retailing literature. The results of the present study will indicate whether immersive VSS experiments lead to authentic shopper behaviour usable by market researchers and in consumer behaviour experiments.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important benefits of online shopping is its convenience [49]. For example, the convenience of product searching, providing different payment Open Journal of Social Sciences methods and options for flexible delivery [50] [51], avoiding traffic to physical stores and competing with other shoppers [52]. According to mental accounting theory, greater convenience means the consumption of mental and physical energy in getting the product will be reduced, thus saving time and effort to improve the effectiveness of the transaction utility [53].…”
Section: Perceived Valuementioning
confidence: 99%
“…Analysis of the shopping cart can provide a valuable information about the needs and behavior of on-line and offline consumers. We can find many researches in the area of: what (and when) is being purchased [15] [19], shopping basket size and value analysis [16], effect of sales promotions on shopping basket [17][18], the cart filling time [20], the influence of smart shopping card on shopping behavior [21], or determinants of consumers' online shopping cart abandonment [22][23] [24].…”
Section: Shopping Basket Analysismentioning
confidence: 99%
“…Anesbury, Nenycz-Thiel, Dawes and Kennedy [20] examined in details behavior of 40 shoppers by recording (screen recording) online shopping trip of new, inexperienced grocery customers. They concluded that shopping process is quite fast.…”
Section: Shopping Basket Analysismentioning
confidence: 99%
See 1 more Smart Citation